Korean immigrants’ perceptions of library services and library multicultural programs for Asian communities before and during COVID-19 - Kim, Yanghee; Kim, Hyun Chu Leah; Kim, Jihye (Frontiers in Education, 2023)
This study explored 141 Korean immigrant parents’ use of local libraries to enhance their families’ social and cultural capital and adjust to the host country. We searched resources in Korean, and multicultural programs planned for the public and immigrants, Asian immigrants in particular, at two libraries before and during COVID-19. Parents reported dissatisfaction with library services because of language barriers (38%) and the lack of Korean resources (38%) and cultural programs (25%). Except for 18 books and 24 e-resources, no library resources in Korean were published after 2008. Before COVID-19, one multicultural program was offered for children. At Branches B and C, the number of adult programs related to Asian culture decreased to 0% from 6% and increased to 3% from 0%, respectively, during COVID-19, when hate crimes against Asians increased by 77%. The respondents’ concerns about the lack of programs supporting their adjustment and fostering multicultural dialogue were validated.